LsNRL4 enhances photosynthesis and decreases leaf angles in lettuce. Issue 10 (22nd July 2022) - An, Guanghui; Qi, Yetong; Zhang, Weiyi; Gao, Hairong; Qian, Jinlong; Larkin, Robert M.; Chen, Jiongjiong; Kuang, Hanhui
Summary: Lettuce ( Lactuca sativa ) is one of the most important vegetables worldwide and an ideal plant for producing protein drugs. Both well‐functioning chloroplasts that perform robust photosynthesis and small leaf angles that enable dense planting are essential for high yields. In this study, we used an F2 population derived from a cross between a lettuce cultivar with pale‐green leaves and large leaf angles to a cultivar with dark‐green leaves and small leaf angles to clone LsNRL4, which encodes an NPH3/RPT2‐Like (NRL) protein. Unlike other NRL proteins in lettuce, the LsNRL4 lacks the BTB domain. Knockout mutants engineered using CRISPR/Cas9 and transgenic lines overexpressing LsNRL4 verified that LsNRL4 contributes to chloroplast development, photosynthesis and leaf angle. The LsNRL4 gene was not present in the parent with pale‐green leaves and enlarged leaf angles. Loss of LsNRL4 results in the enlargement of chloroplasts, decreases in the amount of cellular space allocated to chloroplasts and defects in secondary cell wall biosynthesis in lamina joints. Overexpressing LsNRL4 significantly improved photosynthesis and decreased leaf angles. Indeed, the plant architecture of the overexpressing lines is ideal for dense planting. In summary, we identified a novel NRL gene that enhances photosynthesis and influences plant architecture. Our study provides new approaches for the breeding of lettuce that can be grown in dense planting in the open field or in modern plant factories. LsNRL4 homologues may also be used in other crops to increase photosynthesis and improve plant architecture.